BUDIDAYA IKAN PATIN (Pangasius hypopthalmus) BERBASIS BIOFLOK DENGAN PENAMBAHAN MOLASE PADA RATIO C : N BERBEDA - Fujiana Fujiana; Dewi Nur'aeni Setyowati; Bagus Dwi Hari Setyono (Universitas Mataram, 2020)
This study aimed to analyze the cultivation of catfish (Pangasius hypopthalmus) based on biofloc with the addition of molasses at different C: N ratios. The catfish used was catfish with an initial average length of 6 cm. The container used is a container of 12 pieces with a volume of 40 L and filled with 35 L of fresh water with a stocking density of 15 birds in one container. Molasses was given to the catfish culture medium 2 hours after feeding. The method used in this study was a completely randomized design method (CRD). This study consisted of 4 treatments with 4 replications, namely P1 = Control (without addition of molasses), P2 = C: N ratio media 15, P3 = C: N ratio media 20 and P4 = C: N ratio 25. The results showed that cultivation Biofloc-based catfish (P.hypopthalmus) with the addition of different C: N molasses ratio did not have a significant effect on specific growth rate, absolute growth and survival of catfish. However, the average results showed that the treatment of C: N ratio of media 20 (P3) gave the highest specific growth rates, absolute growth and survival, namely 19.6 gr, 2.26 gr and 62.38%, respectively.